Flouting Maxims in Hitam Putih Talk Show - Lastri Wahyuni Manurung (Balai Bahasa Kalimantan Tengah, 2019)
Communication between speakers and hearer should fulfil maxims in order to have an effective communication and to avoid misunderstanding. In fact, sometimes people flout the maxims. People mostly have reasons behind that and whenever a maxim is flouted there must be an implicature to save the utterance from simply appearing to be a faulty contribution to a conversation. The importance of the research is about finding out the dominant flouting of maxims during the conversation between the participants in Hitam Putih talk show. Besides, the purposes of why flouting the maxim was also displayed as to make this research become more comprehensive. In analyzing the data, the writer uses Grice's theory on maxim. The data were collected by searching, listening and making the transcription, deciding which maxims are flouted based on the criteria, finding the intension of the flouting. As the result, the writer found that the first most flouted maxim is the maxim of quality. The reasons of flouting this maxim are to make a joke and to give a clearer information. In making a joke, a speaker can pretend not to know something, pretend not being honest. Another flouted maxims are also found from the data which are flouting the quantity maxim to give clearer information, to stress something, to avoid unpleasant situation. The relation maxim is also flouted as being polite, and the last the manner maxim is flouted as to make a joke. The characteristic of Indonesian speaker with long winded and not to the point, influence the flouting the maxim. AbstrakDalam peristiwa pertuturan, kadang-kadang penutur dengan sengaja mengabaikan maksim. Perilaku penutur dalam mengabaikan maksim tentu didasari alasan maksud tertentu. Penelitian ini sangat perlu dilakukan untuk menemukan pengabaian maksim yang paling dominan selama perbincangan antarpartisipan dalam acara Hitam Putih. Analisis data menggunakan teori Grice yang berkaitan dengan maksim. Data dikumpulkan dengan cara mencari, menyimak dan mentrasnkripsikan, memperhatikan video, memutuskan maksim apa yang diabaikan berdasarkan kriteria pengabaian dan menemukan tujuan terselubung dalam mengabaikan maksim tersebut. Peneliti menemukan bahwa maksim kualitas adalah maksim yang paling banyak diabaikan. Tujuannya adalah untuk membuat lelucon dan untuk memperjelas informasi. Dalam membuat lelucon tersebut, penutur dapat berlaku pura-pura tidak tahu tentang suatu informasi, berpura-pura untuk berbohong. Maksim lain yang juga diabaikan adalah maksim kuantitas, tujuannya adalah untuk memperjelas sebuah informasi, menegaskan informasi dan untuk menghindari situasi yang kurang nyaman. Maksim relasi juga diabaikan dengan tujuan untuk menjaga kesopanan, dan yang terakhir adalah pengabaian maksim cara untuk menciptakan lelucon. Karakteristik orang Indonesia yang bertele-tele dan tidak mengena langsung pada poin yang dibicarakan, telah mempengaruhi pengabaian maksim yang terjadi.